Distribution and the potential growth of ganitri ( Elaeocarpus ganitrus Roxb ) in Central Java - Asep Rohandi; Gunawan Gunawan (Jurnal Ilmu Kehutanan)
Ganitri (Elaeocarpus ganitrus Roxb) is a multi-purpose species that has the potential to be developed. This species has been known and cultivated by people, particularly in the region of Central Java. The research aimed to identify the distribution of the population and to determine the potentiality of ganitri including the geographic information and ecological conditions. The methods included: (1) the study of literature and direct communication with stakeholders and public, (2) field survey for data collection of performance and productivity of ganitri stands which included : location, spacious, year of planting, stand density, height, diameter, stem form, and planting system (3) primaryand secondary data collections of the site conditions of ganitri plants which included: geographical location, altitude, rainfall, and soil type. The results showed that the ganitri in Central Java was distributed in forest plantations at an altitude of 0-1,300 m abovesea level, on the soil type of regosol, andosol, brown podzolic, latosol with rainfall of 3,500-4,500 mm/year. The distributions of ganitri plantations were found only in some/districts which planted the trees for multi-purposes, which are primarily to produce the seeds as non-timber forest products (NTFPs), to produce construction timber, and to protect the area. The distributions of forest plantations of ganitri in Central Java were found in Cilacap, Kebumen, Kendal, Brebes, Purworejo, Banjarnegara, Wonosobo, Banyumas, Temanggung, Semarang, and Karanganyar district. In general, ganitri plants had a fairly broad ecological range from the highlands to the lowlands, especially in the territory of central and southern of Central Java. Ganitri establishment for seed productions can be found in the District of Cilacap, Kebumen, Purworejo, and Banjarnegara.